Aesthetic Investigation of the Pretarsal Shows and Morphology of Double Eyelids in Chinese Populations: A Questionnaire-based Survey - CHI Yarong; LI Zhujun; JIN Lin; YU Nanze; HUANG Jiuzuo; LONG Xiao (Xiehe Yixue Zazhi)
ObjectiveTo explore the ideal pretarsal shows and morphological characteristics of double eyelids in Chinese populations through a morphometric analysis.MethodsThis study employed a convenience sampling method to survey Chinese adults who did not reside abroad for an extended period (with cumulative overseas stay of over one year). From November 2023 to May 2024, electronic questionnaires were distributed to collect attractiveness ratings of nine different images (including one image featuring single eyelid and eight images with varying pretarsal shows and morphologies of double eyelids). Stratified comparisons were conducted based on gender, age, occupation, etc., to determine the ideal pretarsal show and morphology of double eyelids. Quantitative analysis was performed on the aesthetic features of the nine images depicting double eyelids to validate and elucidate the survey findings.ResultsA total of 493 questionnaires were filled out, and 397 valid questionnaires were included for data analysis after quality control. As for the whole cohort, the images feathering 2 mm double eyelid were deemed to be the most attractive, with the in-fold type scoring (3.72±0.97) points and the out-fold type scoring (3.65±1.04) points. The next was 1 mm, followed by 3 mm, single eyelid, and finally, 4 mm. As for morphology, in-fold type achieved higher scores than out-fold type in images with the same pretarsal show. However, statistically significant differences were only found in ratings for the images with 3 mm and 4 mm double eyelids (all P < 0.05). Stratified analysis based on gender, age, occupation, and other factors yielded results that were largely consistent with those of the overall population.The quantitative analysis of aesthetic characteristics of double eyelids revealed that when the pretarsal show was 2 mm, both the Chen's ratio of the in-fold and out-fold type were 0.630, which closely approximates the golden ratio.ConclusionsThis study validates that the pretarsal show of 2 mm and the presence of either an in-fold or out-fold morphology are considered optimal for double eyelids among Chinese individuals. These findings hold significant implications for the planning of double eyelid surgeries, assessment of surgical outcomes, and evaluation of other periocular procedures associated with double eyelid surgeries.